Perancangan Sistem Informasi Pelaporan Hasil Monitoring Mesin Grinder Berbasis Web - Rian, Hesti; Gustiawan, Handa; Wicaksana, Arifin Wira (Jurnal Teknologi Informatika dan Komputer, 2024)
This study aims to design and build a web-based grinder machine monitoring result reporting information system. The grinder machine is a crucial part of the production process, so monitoring its performance is very important to ensure efficiency and product quality. The information system developed aims to automate the process of collecting, analyzing, and reporting grinder machine performance data. The methodology used in this study includes needs analysis, system design, implementation, and system testing. This system is built using web-based technology to facilitate access and integration with other existing systems in the company. The results of the study show that this information system is able to provide accurate and real-time reports, making it easier for management to make more precise and faster decisions. Thus, it is expected that this system can improve operational efficiency and reduce machine downtime.